First detection and full genomic analysis of Canine Circovirus in CPV-2 infected dogs in Colombia, South America. (2023)
Canine Circovirus (CanineCV) is an emerging virus which since its first report in USA in 2012, it has been described worldwide. It was the second mammalian circovirus species identified in dogs and its role in canine enteritis is still being uncertain as much as its association in disease with the Canine Parvovirus-2 (CPV-2). Here, we aim to confirm for the first time the presence of CanineCV in Colombia and to develop phylogenetic evolutive analyses of CanineCV in CPV-2 positive animals. DNA from samples were extracted and PCR, full genome sequencing and phylogenetic analysis was performed to detect and characterize CanineCV. From a total of 30 CPV-2 positive samples, 16.6% (n = 5) were positives for CanineCV. Sequencing analysis of Colombian CanineCV wild-type strains displayed high identity to each other (99.5-99.7% nt; 99.7% aa). The full genome phylogenetic analysis confirmed that worldwide reported CanineCV strains were separated into four distinct genotypes in addition to a European origin of the South American CanineCV strains. This study demonstrated the importance of continue surveillance of emerging viruses in canine populations and confirm for the first time the circulation and origin of CanineCV in Colombia.